2019
DOI: 10.1186/s12870-019-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of genome-specific repetitive elements in Citrus clementina Hort. Ex Tan. and its taxonomic implications

Abstract: Background Clementine mandarin ( Citrus clementina Hort. ex Tan.) is one of the most famous and widely grown citrus cultivars worldwide. Variations in relation to the composition and distribution of repetitive DNA sequences that dominate greatly in eukaryote genomes are considered to be species-, genome-, or even chromosome-specific. Repetitive DNA-based fluorescence in situ hybridization (FISH) is a powerful tool for molecular cytogenetic study. However, to date few stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…The FISH 5S rDNA oligonucleotide with two signals and (AG 3 T 3 ) 3 with an end signal on every chromosome showed almost no differences among the four walnut cultivars in this study. Similar distribution patterns have also been observed in Citrus species (Deng et al, 2019); Berberis species (Liu and Luo, 2019); and Fraxinus, Syringa, and Ligustrum species (Luo and Liu, 2019a). FISH probes (AG 3 T 3 ) 3 located at chromosome ends ensure accurate chromosome counts (Pereira et al, 2018), although (AG 3 T 3 ) 3 is also occasionally observed in the internal positions of chromosomes (Murray et al, 2002;Majerová et al, 2014;Vasconcelos et al, 2018).…”
Section: Distinguishing Sichuan Walnut Cultivars By Molecular Cellulasupporting
confidence: 67%
See 1 more Smart Citation
“…The FISH 5S rDNA oligonucleotide with two signals and (AG 3 T 3 ) 3 with an end signal on every chromosome showed almost no differences among the four walnut cultivars in this study. Similar distribution patterns have also been observed in Citrus species (Deng et al, 2019); Berberis species (Liu and Luo, 2019); and Fraxinus, Syringa, and Ligustrum species (Luo and Liu, 2019a). FISH probes (AG 3 T 3 ) 3 located at chromosome ends ensure accurate chromosome counts (Pereira et al, 2018), although (AG 3 T 3 ) 3 is also occasionally observed in the internal positions of chromosomes (Murray et al, 2002;Majerová et al, 2014;Vasconcelos et al, 2018).…”
Section: Distinguishing Sichuan Walnut Cultivars By Molecular Cellulasupporting
confidence: 67%
“…At least five molecular genetic linkage maps for walnut have been established (Fjellstrom and Parfitt, 1994;Woeste et al, 1996;Malvolti et al, 2001;Luo et al, 2015;Zhu et al, 2015). Fluorescence in situ hybridization (FISH) with probe-labeled chromosome ends enables accurate counting of small walnut chromosomes (Deng et al, 2019;Liu and Luo, 2019;Luo and Liu, 2019a). Karyotype analysis aids in chromosome physical map construction and chromosome assembly (Hizume et al, 2002;Luo et al, 2017;Luo et al, 2018;Pereira et al, 2018), thereby providing a guide for distinguishing Sichuan walnut cultivars to a certain degree.…”
Section: Introductionmentioning
confidence: 99%
“…Karyotypic features have greatly facilitated taxonomic and systematic studies, and they have also provided important insight into genome size estimations as well as genome structure and organization at the chromosomal level in numerous plant species (Chèvre et al, 2018), including radish (Raphanus sativus L.) (He et al, 2015), Coix lacryma-jobi L. and Coix aquatica Roxb. (Cai et al, 2014), peanut (Arachis hypogaea) (Zhang et al, 2016), sweet potato (Sun et al, 2019), Oleaceae plants (Luo and Liu, 2019), Clementine mandarin (Deng et al, 2019b), and blood orange [C. sinensis (L.) Osb.] (Deng et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…As sequencing technology and associated bioinformatics tools have advanced, citrus genomics have followed suit. Recently, we analyzed the repeat sequence composition in the Clementine mandarin genome and successfully developed a set of FISH probes, encompassing a centromeric-like repeat (CL17), four major satellite repeats (CL1, CL2, CL3, and CL4), two rDNAs (45S and 5S rDNA), and a telomeric repeat (TTTAGGG) n (Deng et al, 2019b). In that study, the physical distribution of these repetitive DNAs on the same somatic metaphase chromosomes of Clementine mandarin and other several citrus cultivars were also analyzed (Deng et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation